Constrained optimization methods for direct blind equalization. - Tsatsanis, M.K (IEEE Journal on selected areas in communications)
Constrained optimization techniques are studied for direct design of linear multichannel equalizers. Novel blind algorithms are derived by minimizing the equalizer's output variance subject to appropriate constraints. The constraints are chosen to guarantee no desired signal cancellation, and their parameters are jointly optimized to maximize the signal component at the output. The resulting blind algorithm was observed to have near optimal performance at high signal-to-noise ratio, i.e., close to the performance of the trained minimum mean-square-error receiver. Also, the proposed method is not sensitive to the color of the transmitted sequence. Analytical expressions are derived to quantify the algorithm's performance